2006
DOI: 10.1056/nejmoa055255
|View full text |Cite
|
Sign up to set email alerts
|

Counseling plus Buprenorphine–Naloxone Maintenance Therapy for Opioid Dependence

Abstract: Among patients receiving buprenorphine-naloxone in primary care for opioid dependence, the efficacy of brief weekly counseling and once-weekly medication dispensing did not differ significantly from that of extended weekly counseling and thrice-weekly dispensing. Strategies to improve buprenorphine-naloxone adherence are needed. (ClinicalTrials.gov number, NCT00023283 [ClinicalTrials.gov].).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
269
1
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 314 publications
(289 citation statements)
references
References 27 publications
18
269
1
1
Order By: Relevance
“…21 The findings of significant superiority of buprenorphine compared to naltrexone for retention and time to resuming heroin use are unique. The results for buprenorphine treated patients in this study regarding retention and maximum duration of opioid abstinence are similar to previous studies of buprenorphine, 19 and the results for naltrexone treated patients were comparable to the results of many studies, 24,33,34 suggesting that the findings regarding the greater efficacy of buprenorphine compared to naltrexone or placebo may generalize to other populations and settings.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…21 The findings of significant superiority of buprenorphine compared to naltrexone for retention and time to resuming heroin use are unique. The results for buprenorphine treated patients in this study regarding retention and maximum duration of opioid abstinence are similar to previous studies of buprenorphine, 19 and the results for naltrexone treated patients were comparable to the results of many studies, 24,33,34 suggesting that the findings regarding the greater efficacy of buprenorphine compared to naltrexone or placebo may generalize to other populations and settings.…”
Section: Discussionsupporting
confidence: 88%
“…Post-hoc comparisons indicated that buprenorphine-treated patients achieved longer maximum consecutive days of opiate abstinence compared to placebo-treated patients (p<0.01); the differences between buprenorphine and naltrexone (p=0. 19) and between naltrexone and placebo (p=0.18) were not significant.…”
Section: Heroin Use and Abstinencementioning
confidence: 81%
See 2 more Smart Citations
“…A key difference between this program and more traditional integrated programs was the ability to provide buprenorphine/naloxone (BPN/NLX, also known by the brand name suboxone), an opioid agonist treatment which has been shown to be effective for improving substance use outcomes in primary care settings. 52 In this qualitative study, using focus group and satisfaction survey data collected throughout the course of the program, we identify how patients view an integrated model of care, evaluate the key elements to its success and provide recommendations for other programs.…”
mentioning
confidence: 99%